Indagação interdisciplinar no pátio da escola (IIPE) e educação midiática aplicadas à educação ambiental na educação básica - Pereira, Gabriele (Universidade Federal de São Carlos, 2025)
Environmental education in basic education faces challenges related to students' lack of interest and the alarmist approach to environmental issues. To make teaching more engaging and meaningful, this research evaluated the application of Interdisciplinary Inquiry in the Schoolyard (IIPE) combined with Media Education in a public school in São Carlos/SP, Brazil. The methodology adopted was action research, with workshops involving schoolyard observation, question formulation, data collection, and the production of audiovisual materials by students. The activities aimed to stimulate curiosity, interaction with the environment, and the use of digital media. The results indicated that IIPE promotes more active and participatory learning, expanding students' perception of nature in their surroundings. However, challenges such as immaturity in the use of technology and the traditional school structure limited students' autonomy. Media Education proved promising but requires guidance to be effectively integrated into the pedagogical process. The research concludes that the combination of these methodologies can make environmental education more accessible and dynamic, provided that teachers receive adequate support and that the approach is adapted to students' needs.
Interdisciplinary inquiry in the schoolyard (IIPE) and media education applied to environmental education in basic education
Keywords: Aprendizagem ativa; Ciclo de indagação; Metodologias ativas; Sensibilização ambiental; Aprendizagem investigativa; Active learning; Inquiry cycle; Active methodologies; Environmental awareness; Investigative learning; CIENCIAS BIOLOGICAS